Analisis Optimalisasi Waktu dan Biaya dengan Penambahan Jam Metode Time Cost Trade Off - Mahendra, Muhammad Oka; Saputro, Teguh Eko; Putra, Al Fiillian Sah (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Construction projects are bound by predefined schedules and budgets established from the outset. This study aims to optimize time and cost through a 3-hour daily overtime intervention, focusing on evaluating schedule acceleration effectiveness and resource efficiency. The Time Cost Trade Off (TCTO) method was applied via crashing techniques, systematically calculating cost-time trade-offs. Analysis centered on critical paths identified using the Critical Path Method (CPM), with schedule compression achieved through additional work hours. The findings reveal that the project duration was reduced from 180 days to 145 days, achieving a 35-day reduction (19.4%). This outcome demonstrates that targeted overtime interventions on critical activities optimize time allocation without compromising cost control, while affirming the relevance of the TCTO-CPM integrated approach in construction project management. overtime wages.